Injury occurrence in male handball players and its impact on physical constitution - Salzer, S.; Heansel, R.; Rey, J.; Maltry, L.; Holzgreve, F.; Lampe, J.; Wanke, E. M.; Groneberg, D. A.; Ohlendorf, D. (International Journal of Sports Medicine, 2020)
In male handball, limited knowledge exists about the body posture and postural control in correlation to their injury occurrence and their impact on physical constitution. 91 male handball players participated and were asked about playing position and years, NSAIDs intake, sustained injuries and therapy duration. A three-dimensional back scanner and a pressure measuring plate were used. Shoulder injuries cause a differing scapular height and increase the vertebrae rotation in correlation to playing years. Lower limb injuries lead to a decrease on the Centre of Pressure (CoP) with growing game experience. Wing players show the lowest injury risk. Lower limb and shoulder girdle are mostly affected regarding the incidence of injuries. Pivot players suffer most injuries in the lower limb area (59%), whereas wing players mostly have shoulder injuries (19%). Being injured, 21% of the players continue playing, 79% pause for a minimum of six months (25%). No correlation can be determined between level of profession, use of NSAIDs and body posture or postural control. Playing position, employment situation or NSAIDs have no influence on type of injury, body posture or postural control. While shoulder injuries can be recognized in the vertebrae area, lower limb injuries can affect the CoP.